(untitled) (Journal of Medical & Health Sciences Review, 2025)
All living things, including bacteria and human being, have ATP-binding cassette (ABC) proteins. An extensive class of proteins known as ABC transporters is responsible for transferring a variety of substrates across cell membranes. The modular structure of ABC transporters varies, and they can have any domain arrangement, ranging from complexes of four distinct single domain polypeptides to a single four domain polypeptide. Human P-glycoprotein (ABCB1 and P-gp) is a multi-specific drug, efflux transporters which mediate the resistance of cancer cells to cytotoxic drugs. Several synthetic inhibitors ABCB1 are failed in phase III clinical trials therefore there is an urgent need of new inhibitor from natural resource. In this regard current study was conducted to evaluate solvent-solvent extraction and phytochemicals from Colpomenia sinousa and Iyengaria phaeophycota against MDR ABCB1 transports. All samples were evaluated for antioxidant (DPPH) assay and MTT assay for the inhibition of ABCB1 transpoter. Ethanol, ethyl acetate and methanol of Colpomenia shown the lower IC50 value of 14.69±0.01µg/mL, 30.01± 0.2.5µg/mL and 48.02±3.20µg/mL respectively for antioxidant assay, the sample of Iyengeria also shown high inhibition with IC50 of 16.80±0.01 µg/mL, 31.73±0.23µg/mL, 35.84±0.618µg/mL and 40.80±0.241µg/mL for ethanol, n-Hexane, methanol and ethyl acetate respectively. Further active samples were assessing in ABCB1 inhibition assays. The results from the above methodology shown potent inhibition for ABCB1 transporters. ABC transporter shows the expression with IC50 29.57 ±2.128µg/mL, 77.12±3.21 µg/mL and 45.33±0.032µg/mL for Iyengeria ethanol, ethyl acetate and methanol respectively to attenuate accumulation of cellular and tissue drugs that increase MDR across a different type of cancers. One goal is to overcome MDR in order to increase patient survival.